PENGARUH BAURAN PROMOSI DAN CITRA PERUSAHAAN TERHADAP MINAT BELI KEMBALI PRODUK VIZCAKE PEKANBARU - Dewi, Zulfa Kurnia; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The promotion mix is the company's efforts to inform, persuade, and remind consumers of the company's brands and products. The consistent and effective promotion mix can awaken and remind consumers of the existence of a product and can also grow the company's image. Corporate image is a set of beliefs and impressions that consumers have of a company. A good and positive corporate image is a competitive advantage in realizing the company's goals. Success in realizing the company's goals starts from the consumer's interest to make a buy back. Repurchase intention is the desire of consumers to buy back a product or service based on the impression and experience of a consumer to a company.This research was conducted at Vizcake Pekanbaru store which located at general road Sudirman No. 418 Pekanbaru. The problem in this research is not achieving the company's sales target in the last five years and the percentage of sales target achievement decreased in three consecutive years and the least increase of consumer number. This is allegedly influenced by repurchase intention.The purpose of this study is to determine the effect of promotion mix and corporate image on the repurchase intention Vizcake Pekanbaru product. In this research the method used is descriptive quantitative with SPSS program. The sample of this study was taken as many as 100 respondents from the total population 31.879 calculated using slovin formula. Methods of data collection using questionnaires. Hypothesis testing using multiple linear regression analysis method.The results showed that the promotion mix and the image of the company have a significant effect on the repurchase intention Vizcake Pekanbaru product.Keywords: Promotional Mix, Corporate Image, Repurchase Intention.